Analisis keterkaitan jumlah hasil panen padi terhadap PDRB Provinsi Lampung menggunakan analisis input-output - Febrianti, Werry; Triana, Shakila Syafa (Nur Science Institute, 2024)
The agricultural sector has an essential economic position, especially in developing countries. In Indonesia, rice is one of the primary commodities that meets food needs and increases regional income. Economic growth is influenced by interactions between economic sectors, including the agricultural industry. The input-output analysis method is used to assess the relationship between sectors and the impact of changes in the farming sector on the economy as a whole. This research explores the influence of rice harvest on Gross Regional Domestic Product (GRDP) through an input-output analysis approach. The research results indicate that increasing rice yields affects the agricultural sector's input-output value and final demand, impacting the GRDP of Lampung Province.